Proceedings of the 2017 5th International Conference on Frontiers of Manufacturing Science and Measuring Technology (FMSMT 2017 2017
DOI: 10.2991/fmsmt-17.2017.119
|View full text |Cite
|
Sign up to set email alerts
|

A Vulnerability Mining System Based on Fuzzing for IEC 61850 Protocol

Abstract: Abstract. In this paper, we proposed an effective vulnerability mining system for IEC61850 protocol in the Smart Grid. First of all, we introduce the basic structures and features of IEC61850 protocol. Next, we summarize the possible vulnerabilities of it. Finally a fuzzing tester named IECFuzzer is designed and implemented using the technique of fuzzing. A lot of simulation results show that IECFuzzer can not only be used to exploit the potential denial-of-service vulnerabilities of IEC61850 protocol, but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This research has demonstrated that the GOOSE protocol of IEC 61850 entails vulnerabilities and is prone to malicious attacks even under the compliance of the IEC 62351 security standard; these vulnerabilities need to be addressed in subsequent standards and protocol revisions. Reference [100] introduces a fuzzing tester termed as "IECFuzzer" which can be used to exploit the potential denial-of-service vulnerabilities of IEC61850 protocol, but also to verify the robustness of PLC devices using IEC61850 protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research has demonstrated that the GOOSE protocol of IEC 61850 entails vulnerabilities and is prone to malicious attacks even under the compliance of the IEC 62351 security standard; these vulnerabilities need to be addressed in subsequent standards and protocol revisions. Reference [100] introduces a fuzzing tester termed as "IECFuzzer" which can be used to exploit the potential denial-of-service vulnerabilities of IEC61850 protocol, but also to verify the robustness of PLC devices using IEC61850 protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Our future work will include the security analysis of additional software in the power grid domain, as well as the examination of software in other domains. We also plan to consider the combined assessment of results concerning communication protocol security through relevant simulation-based tools (e.g., Scyther) on the one hand (e.g., [99][100][101]), and results from the software implementation security assessment on the other hand, towards the computation of a comprehensive risk level of 5G and smart grid systems. Finally, the effectiveness of model-based checking tools such as [93][94][95] in the identification of security-related issues, and the interplay between secure software development practices and the operation of forensics in the domain of 5G and Smart Grid computing [107] will be studied.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies published regarding the creation of fuzzing data (Ai-Fen Sui et al, 2011;Blumbergs and Vaarandi, 2017) and testbeds (Yang et al, 2015;Mathur and Tippenhauer, 2016) where the ICS devices can be tested, but they rarely explore the indication of the corruption of the inspected device. Tu et al (2017) introduced the IECFuzzer containing four modules: the mutator module, the mutator selection module, the data reorganisation module and the survival verification module. Here the survival verifier module communicates with the target PLC in real-time and obtains the status of the PLC.…”
Section: Related Workmentioning
confidence: 99%
“…At present, the commonly used vulnerability mining techniques are divided into static analysis, dynamic analysis, binary comparison, fuzzy testing, and so on [6][7][8][9][10][11][12]. Fuzzy testing has the advantages of high automation, low system consumption, low false-alarm rate, and being independent of the source code of the object program [7].…”
Section: Introductionmentioning
confidence: 99%